Pneumonia as a viral complication or secondary bacterial infection in a pediatric measles? A case report - Komang Andjani Putri; Raihanah Yusuf (Pediatric Sciences Journal, 2026)
Background: Measles is a highly contagious acute viral infection worldwide. Pneumonia is one of the major respiratory complications associated with measles and remains a leading cause of mortality. Pneumonia in measles may occur because of primary viral complications or secondary bacterial infection. Case Presentation: A three-year-old girl presented with fever, generalized erythematous rash, conjunctival injection, cough, coryza, and shortness of breath. Physical examination revealed erythematous papules across the body, bilateral lung rhonchi, Koplik spots, and hyperemic conjunctivae. Complete blood count showed a normal white blood cell count with neutrophilia. The patient was diagnosed with measles-associated pneumonia and treated with vitamin A supplementation, antibiotics, and supportive care. She was hospitalized for five days with progressive improvement in respiratory problems and skin rash. Pneumonia in measles may develop from initial viral complications or measles-induced immunosuppression, predisposing individuals to secondary bacterial infection. In this case, an increased neutrophil-to-lymphocyte ratio was observed, which may reflect an inflammatory response and raise the suspicion of possible secondary bacterial infection. However, neutrophil to lymphocyte ratio is a non-specific marker that can also be elevated in severe viral infections, systemic inflammation, physiological stress, and corticosteroid exposure. Therefore, its interpretation should be made cautiously and in conjunction with other clinical findings. Conclusion: The neutrophil to lymphocyte ratio is a simple and accessible laboratory parameter that may support clinical assessment but cannot independently confirm bacterial infection. Comprehensive assessment involving clinical, laboratory, and radiological findings is essential to support therapeutic decision-making in pediatric patients with measles-associated pneumonia.